(untitled) (Research, Society and Development, 2022)
The present article is situated in the theoretical-practical context of Social Pedagogy, Didactics, and social-community insertion, and aims to analyze and reflect on the author’s experiences in the mentioned fields, dialoguing with the body of knowledge of the mentioned areas. From a qualitative approach and the methodology of the experience report, the author focused on the relationship between teaching practice, higher education, and its social and communitarian insertion, weaving an implicit dialogue of theoretical and practical character between Didactics and Social Pedagogy. It sought to reflect on some contents and theoretical references of Didactics, emphasizing its contributions to the professional practice of the author and the formation of students. It is known that Social Pedagogy brought many contributions to Pedagogy, considering that the latter, as far as the Brazilian academic tradition is concerned, has always been induced in its studies to focus more on school instruction processes, which restricted the theoretical and methodological reach of the referred science, being almost always associated to the school area. The paper walks through this background issue and focuses on the relevance of Social Pedagogy, in the dialogue and interface with Didactics, showing in the educational practice and training processes experienced by the author how this area can produce a set of reflections that problematize training and pedagogical practice, bringing to light dimensions of education beyond technical, instructional, and school issues. The reflections and analysis of the experience in question pointed to the understanding that Social Pedagogy, in its relationship with Didactics, can contribute to the production of knowledge and ground skills and competencies that amplify the possibilities of knowledge and appropriation of the reality of education.